1992
DOI: 10.2134/agronj1992.00021962008400060034x
|View full text |Cite
|
Sign up to set email alerts
|

Plot Sprinklers for Irrigation Research

Abstract: Portable plot sprinklers were developed that allowed individual plots to be irrigated independently of other plots. Each plot sprinkler consisted of three rotary‐pendulum, square‐pattern sprinkler heads mounted on a PVC pipe frame. Plot sprinkler water output was 0.9 m3 h−l, on an area 4.6 m wide by 13.7 m long, with Cu = 80%, when operated at 86 kPa. Plot sprinklers were used to apply irrigation treatments In a randomized block design to evaluate potato (Solanum tuberosum L. ‘Russet Burbank’) tuber quality re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…They reported that reducing irrigation supply resulted in reduced yield and quality. Similarly, research conducted by Eldredge et al (1992), Lynch et al (1995) and Shock et al (1993) showed that reductions in tuber yield and quality could result from a brief period of water stress. Other studies have indicated that yield and quality of potato could be improved with drip irrigation and optimal irrigation scheduling (Singh et al, 1977;Erdem et al, 2006).…”
Section: Introductionmentioning
confidence: 92%
“…They reported that reducing irrigation supply resulted in reduced yield and quality. Similarly, research conducted by Eldredge et al (1992), Lynch et al (1995) and Shock et al (1993) showed that reductions in tuber yield and quality could result from a brief period of water stress. Other studies have indicated that yield and quality of potato could be improved with drip irrigation and optimal irrigation scheduling (Singh et al, 1977;Erdem et al, 2006).…”
Section: Introductionmentioning
confidence: 92%
“…Eldredge et al (1992Eldredge et al ( , 1996 demonstrated that the severity of a single water stress episode progressively increased both poorly formed tubers and sugar ends. Secondary growth may be induced by any condition favoring vegetative growth Bodlaender et al 1964).…”
Section: Physiological Mechanismsmentioning
confidence: 99%
“…Nitrogen loss to groundwater and soil losses in terms of sediment in runoff are aggravated by over-irrigation. Under-irrigation of potato and onions leads to losses in yield and quality (Eldredge et al 1992(Eldredge et al , 1996Shock and Feibert 2002;Shock et al 1993bShock et al , 1998bShock et al , 2000aShock et al , 2002a. Irrigating only when a crop needs water means that less water is used, less energy is used for pumping, less nitrogen is leached preventing additional groundwater pollution, and both crop yield and quality can be higher.…”
Section: Irrigation Managementmentioning
confidence: 99%
“…Criteria for irrigation Soil water criteria for irrigating vary depending on the crop, the type of soil, and the type of irrigation (Shock et al 2007c;Shock and Wang 2011). For Malheur County, the criteria for different crops' needs have been developed at the Malheur Experiment Station of Oregon State University (Eldredge et al 1992(Eldredge et al , 1996Shock and Feibert 2002;Shock et al 1993bShock et al , 1998bShock et al , 2000aShock et al , 2002aShock et al , b, 2007cThompson et al 2008). Soil moisture monitoring devices When irrigation criteria based on soil moisture have been established, an easy, reliable method of measuring soil water is essential for grower adoption of this irrigation scheduling technique.…”
Section: Irrigation Managementmentioning
confidence: 99%